High Photosynthetic Rate of a Chlorophyll Mutant of Cotton - Benedict, C. R. (1972)
In a chlorophyll mutant (virescent) and wild-type cotton (Gossypium hirsutum L.), a number of photosynthetic parameters have been measured and compared with those published for other chlorophyll mutants. (a) The photosynthetic rates at 230 w/m(2) (400-700 nm) from a tungsten lamp were 36.8 mg CO(2) fixed/dm(2)·hr (virescent) and 39.5 mg CO(2) fixed/dm(2)·hr (wild-type). On a chlorphyll basis, the photosynthetic rates were 36.8 and 12.1 mg CO(2) fixed/mg chl·hr, respectively. (b) The photosynthetic rates at 13 w/m(2) (400-700 nm) from a tungsten source were 7.1 mg CO(2) fixed/dm(2)·hr (virescent) and 7.4 mg CO(2) fixed/dm(2)·hr (wild-type). On a chlorophyll basis, the photosynthetic rates were 6.0 and 1.4 mg CO(2) fixed/mg chl·hr, respectively. (c) The chlorophyll a/b ratios of the virescent and wild-type leaves were 3.3 and 4.1 (d) The chlorophyll/carotenoid ratios for the virescent and wild-type leaves were 3.2 and 7.3, respectively. (e) The photosynthetic carbon metabolism of the chlorophyll mutant was through the reductive pentose phosphate cycle. (f) The CO(2) compensation points for the virescent and wild-type plants were similar. (g) The mutant and wild-type leaves have the same quantum yield in the red part of the visible spectrum, but the virescent leaves have a lower quantum yield in the blue part of the spectrum. (h) Virescent and wild-type leaves contain similar levels on a protein basis of several reductive pentose phosphate cycle enzymes.